The effect and safety of intravitreal injection of ranibizumab and bevacizumab on the corneal endothelium in the treatment of diabetic macular edema. (2nd January 2017) - Guzel, Huseyin; Bakbak, Berker; Koylu, Mehmet Talay; Gonul, Saban; Ozturk, Banu; Gedik, Sansal
Abstract: Objective : To investigate the effect and safety of intravitreal injection (IVI) of bevacizumab and ranibizumab on corneal endothelial cell count and morphology in patients with diabetic macular edema. Materials and methods : A total of 60 eyes from 60 consecutive patients who received 0.5 mg/0.05 ml IVIs of bevacizumab ( n  = 30, IVB group) or 1.25 mg/0.05 ml ranibizumab ( n  = 30, IVR group) for three consecutive months were investigated prospectively. Specular microscopy was performed to evaluate endothelial cell count, the percentage of hexagonal cells (pleomorphism), and the coefficient of variation of the cell size (polymegathism); optical biometry was performed to evaluate central corneal thickness. Results before injection and 1 month after the first and third injections were compared. Results : The groups were matched for age ( p  = 0.11) and gender ( p  = 0.32). There was no significant difference in endothelial cell count (IVB group, p  = 0.66; IVR group, p  = 0.74), pleomorphism (IVB group, p  = 0.44; IVR group, p  = 0.88) and polymegathism (IVB group, p  = 0.21; IVR group, p  = 0.24) before injection or 1 month after the first and third injections. There was also no difference in central corneal thickness (IVB group, p  = 0.15; IVR group, p  = 0.58) before injection or 1 month after the first and third injections. Conclusion : Monthly 1.25 mg/0.05 ml IVIs of bevacizumab or 0.5 mg/0.05 ml of ranibizumab for three consecutive months in the treatment of diabetic macular edema does not affect corneal morphology and has no harmful effects on the endothelium.